Preliminary Insights into the Adoption of CGIAR-Related Agricultural Innovations in Vietnam - Kosmowski, Frederic; Bach, Thao; Nguyen, Oanh; Stevenson, James R.; Visaria, Sujata (2023)
Over the past two decades, Vietnam’s GDP per capita has grown ninefold. Concurrently, its agricultural sector has transformed to a strong commercial orientation. At the same time that the share of agriculture in GDP fell from 24.5 percent to 12.6 percent, agricultural value-added grew sixfold from USD 7.5 bn to USD 46 bn (World Bank, 2022). This suggests that Vietnam could provide contemporary insights into agricultural innovation coinciding with – and possibly contributing to – economic growth. Vietnam is also a high-priority country for CGIAR research. Since 2021, the Standing Panel on Impact Assessment (SPIA) has been conducting a country study of the impact of CGIAR-related agricultural innovations in Vietnam. As in the other countries where this country-level approach was pioneered and developed, this process began with desk research and key informant interviews to generate a stocktake or information about all CGIAR-related innovations that may have been disseminated or adopted at scale. From a longlist of 79 innovations across multiple domains, the SPIA Vietnam team found indications that 18 may have diffused at scale.